Czy trudno być dobrym profesorem?O wartościach związanych z etosemnauczyciela akademickiego (Heteroglossia – studia kulturoznawczo-filologiczne, 2025)
The aim of the article is an attempt to determine the repertoire of features that, for students, are currently the essence of the ethos of an academic teacher. Tools related to the survey, philological and axiolinguistic methods were used. On this basis, specific types of values in the scientific, didactic and organizational spheres were identified. Pragmatic, cognitive and social values achieved the highest position. Issues related to the examination of values (resulting from the survey) require further, more detailed research.